'L'État c'est moi' … ou quoi? On the interrelations of accounting, managing and governing in the French 'administrative monarchy': revisiting the Colbert (1661–1683) and Paris brothers (1712–1726) episodes. (1st September 2016) - Hoskin, Keith; Macve, Richard
ABSTRACT: We explore the genesis of the modern power of management and accounting, reviewing two historical episodes that have been claimed to embody aspects of this modernity. For our analysis, we distinguish two aspects of double-entry bookkeeping (DEB): first, the basic bookkeeping technique of cross-referencing and analysing doubled entries, and second, 'the full logic' of a closed system tracking an entity's income and expense, assets and liabilities, and 'capital'. Our first episode is Jean-Baptiste Colbert's 'governing by inquiry' (1661–1683), understood as a 'managing' of the French 'administrative state' under Louis XIV, where we see DEB's use as limited to the first technique, undertaken for a forensic auditing of tax revenues to control and amend bad conduct. Second is the episode (1712–1726) of a banking family, the Paris brothers, where DEB is again first deployed similarly, for auditing and control of tax farmer practice, but then proposed as more general means of managing/governing the state. We review the interpretations of the first of these episodes made by Miller and Soll, and that of Lemarchand concerning the second. We draw on Foucault's analysis of today's forms of governing as a 'governmental management', which was blocked in the era of the administrative state, and explain this blockage as a result of principal–agent structures being used to govern the state. In this light, we see Miller as over-interpreting the closeness of Colbert's 'governing by inquiry' to modern 'governmentality', and Soll as over-interpreting modern forms of management and accounting as operative in the governing approach of Colbert as 'Information Master'. We also re-analyse the effective reach of the ambitions of the Paris brothers, as set out by Lemarchand, for the deployment of DEB. We then draw on Foucault's and Panofsky's analyses of 'inquiry' as a 'form of truth' which began as a new twelfth-century way of thinking, and trace this to Abelard's development of ' inquisitio ' as a new 'critical reading'. We characterise its modus operandi as a 'graphocentric synopticism', graphocentric since all 'data' are translated into a gridded, cross-referenced über-text, which is then readable synoptically, all-in-one, from an immobile synthesising position. Foucault suggests that 'inquiry' gives way as mode of truth to 'examination' around 1800, and we link the genesis of governmental management to this shift and to the consequent articulation of a 'panopticism' which is multiply semiotic and so 'grammatocentric'.